A Phenomenological Analysis of Shame. Issue 2 (3rd April 2017) - Shaoming, Chen
EDITOR'S ABSTRACT: This article presents a phenomenological analysis of several Chinese notions of shame—embarrassment (xiu), chagrin (kui), shame (chi), and disgrace (ru) . It elaborates on their structural connections and related experiences, more particularly concerning interpersonal conditions and emotional or physical reactions. Chen focuses on the notion of moral shame, its connection to the Confucian tradition, and its weakening in the current society, due to ideational and technical circumstances, such as the increased sense of individual self and the booming of internet culture.